2016
DOI: 10.1103/physreva.94.062504
|View full text |Cite
|
Sign up to set email alerts
|

Short-range photoassociation of LiRb

Abstract: We have observed short-range photoassociation of LiRb to the two lowest vibrational states of the d 3 Π potential. These d 3 Π molecules then spontaneously decay to vibrational levels of the a 3 Σ + state with generation rates of ∼ 10 3 molecules per second. This is the first observation of many of these a 3 Σ + levels. We observe an alternation of the peak heights in the rotational photoassociation spectrum that suggests a p-wave shape resonance in the scattering state. Franck-Condon overlap calculations pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…In the present case, due to initial ultracold temperature following laser cooling, free 87 Rb atoms will collide in the pure s-wave scattering regime through the a u 3 S + molecular potential, which is properly described by the Hund's case b. The initial state thus processes even parity [39], N=0 rotational quantum number and J=1 total angular momentum quantum number. The PA-excited molecular state in 1 g 3 P , on the other hand, is better described in the Hund's case c with the triad J M ¢W¢ ¢ñ | .…”
Section: Level Scheme For Pa and Ground State Molecule Synthesismentioning
confidence: 90%
See 2 more Smart Citations
“…In the present case, due to initial ultracold temperature following laser cooling, free 87 Rb atoms will collide in the pure s-wave scattering regime through the a u 3 S + molecular potential, which is properly described by the Hund's case b. The initial state thus processes even parity [39], N=0 rotational quantum number and J=1 total angular momentum quantum number. The PA-excited molecular state in 1 g 3 P , on the other hand, is better described in the Hund's case c with the triad J M ¢W¢ ¢ñ | .…”
Section: Level Scheme For Pa and Ground State Molecule Synthesismentioning
confidence: 90%
“…As an example, we consider 87 Rb 2 diatomic molecules, whose PA spectroscopy and TDMs are known in the literature [22,36,37], although we emphasize that this scheme can be extended to other bi-alkali molecules presenting short-range PA pathways [38][39][40]. Specifically, we calculate the vibrational states of 87 Rb 2 associated with the relevant potential energy curves taken from [36] using the Numerov method 3 .…”
Section: An Example: Transition Dipole Moment (Tdm) Of Rb 2 Diatomic mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several years, a series of studies showed that short-range PA is generally possible for bi-alkali molecules: short-range PA has been demonstrated for NaCs [9], Rb 2 [10,11], LiCs [12], RbCs [13][14][15], and LiRb [16,17]. Furthermore, production of rovibronic groundstate has been verified for LiCs [12], RbCs [14,15], and LiRb [17].…”
Section: Introductionmentioning
confidence: 99%
“…For the long-range PA, the collision atoms with low collision energy mainly form alkali-metal molecules, such as Rb 2 , Cs 2 , Li 2 , Na 2 , LiRb, RbCs, NaCs, and LiCs [9][10][11][12] . The short-range PA for alkali-metal molecules also has been studied both theoretically and experimentally [13][14][15][16][17] . The short-range PA with high energy collision has been proposed theoretically and its products include OH, HBr, HF, HI, and NaH [8,18,19] .…”
mentioning
confidence: 99%